Definition and documentation of traditional foods of the Black Sea Area Countries: potential nutrition claims. (4th July 2013) - Dilis, Vardis; Vasilopoulou, Effie; Alexieva, Iordanka; Boyko, Nadiya; Bondrea, Aurelian; Fedosov, Sergey; Hayran, Osman; Jorjadze, Mariam; Karpenko, Dmitry; Costa, Helena S; Finglas, Paul; Trichopoulou, Antonia
Abstract BACKGROUND Nutrition and health claims are permitted in foods marketed in the European Union under Regulation 1924/2006. Quality products such as traditional foods might benefit from this act, as it can highlight their nutritional richness. In this study the nutritional content of 33 traditional foods from the Black Sea Area Countries was evaluated against the thresholds of the Regulation for nutrition claims. RESULTS Most of the foods were eligible to bear several nutrition claims, mostly related to their fat, sugar, fiber and sodium content. The average number of claims per traditional food was two, with a range between zero and nine. Overall, about 72 nutrition claims were potentially relevant for the 33 traditional foods studied. Foods linked with the most claims were nuts and seeds. CONCLUSION The inclusion of traditional foods under this standardized European scheme could be an efficient way to highlight their possible beneficial nutritional properties. The production and marketing of traditional foods could be of benefit to both the health of consumers and the economic viability of producers, especially small‐ and medium‐size enterprises. © 2013 Society of Chemical Industry